Penanggulangan Kriminalitas Di Desa Cikoang Kec. Mangarabombang Kab. Takalar - Ibraya, Nurfadilah Syawal; Mukramin, Sam'un (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
Indonesia is the largest country in Southeast Asia. However, most Indonesian citizens still commit crimes. Crime or crime is an act that violates the laws, regulations, norms and values that apply in society. These crimes can harm and threaten the safety and life of a person. Crime itself grows because of crimes in a person such as murder, violence, murder, theft, robbery, robbery, fraud, persecution, theft of substances and drugs, and many others. Meanwhile, from a sociological point of view, crime is treated as an act that deviate from the values or norms prevailing in society. Criminology (criminology) comes from the words crimen (crime) and logos (knowledge or science). As for criminality, as a social problem, social action is carried out by individu…Indonesia is the largest country in Southeast Asia. However, most Indonesian citizens still commit crimes. Crime or crime is an act that violates the laws, regulations, norms and values that apply in society. These crimes can harm and threaten the safety and life of a person. Crime itself grows because of crimes in a person such as murder, violence, murder, theft, robbery, robbery, fraud, persecution, theft of substances and drugs, and many others. Meanwhile, from a sociological point of view, crime is treated as an act that deviate from the values or norms prevailing in society. Criminology (criminology) comes from the words crimen (crime) and logos (knowledge or science). As for criminality, as a social problem, social action is carried out by individu…Title in English. An abstract is a brief summary provides information about the public service; 1) background; 2) partner problems; 3) purpose of devotion; 4) method of devotion; 5) results of devotion; 6) conclusion; and 6) suggestions.